2022
DOI: 10.1111/wvn.12599
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare consumers' and professionals' perceived acceptability of evidence‐based interventions for rural transitional care

Abstract: Background: There is a pressing need for high quality hospital-to-home transitional care in rural communities. Four evidence-based interventions (discharge planning, treatments, warning signs, and physical activity) have the potential to improve rural transitional care. However, there is limited understanding of how the perceptions of healthcare consumers and professionals compare on the acceptability of the interventions. Convergent views on intervention acceptability support implementation, whereas divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The scale has demonstrated internal consistency reliability (alpha > .80) [ 23 26 ] as well as content, discriminant [ 25 , 26 ] and factorial validity (factor loadings > .30) [ 25 ] in prior research on different health interventions and populations. In the larger study, the scale had Cronbach alphas ranging from 0.85 to 0.89 across the four interventions [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The scale has demonstrated internal consistency reliability (alpha > .80) [ 23 26 ] as well as content, discriminant [ 25 , 26 ] and factorial validity (factor loadings > .30) [ 25 ] in prior research on different health interventions and populations. In the larger study, the scale had Cronbach alphas ranging from 0.85 to 0.89 across the four interventions [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the transition from hospital to home constitutes a marked shift from provider-driven to self-managed care for rural patients. After hospital discharge, many patients and their families find themselves managing care previously provided by nurses in hospital (e.g., watching for worsening health conditions), typically with minimal training and professional guidance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In our prior research, older rural medical patients at risk for hospital readmission and their families indicated that their most pressing unmet TC need was knowing how to recognize and address the signs of worsening health conditions [6][7][8]. Evidence indicates that patients typically receive little preparation in this regard and require more education prior to discharge on whether a sign or symptom necessitates professional intervention [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations